The relationship of physical exercise and suicidal ideation among college students: a moderated chain mediation model - Jinrui Zhou; Feng Sun (Frontiers in Psychology)
BackgroundThis study examines the impact of physical exercise on college students’ perceived social support, meaning in life, and suicidal ideation, and further investigates the mediating and sequential mediating roles of perceived social support and meaning in life in the association between physical exercise and suicidal ideation, additionally exploring the moderating role of gender.MethodsA total of 545 Chinese college students completed the Physical Activity Rating Scale-3 (PARS-3), Perceived Social Support Scale (PSSS), Meaning in Life Questionnaire (MLQ), and Self-rating Idea of Suicide Scale (SIOSS). A bias-corrected percentile bootstrap approach was applied to assess the sequential mediating effects of perceived social support and meaning in life on the relationship between physical exercise and suicidal ideation.Results(1) Physical exercise and suicidal ideation were negatively correlated (r = −0.296, p < 0.01). A significant direct effect of physical exercise on suicidal ideation was also detected (β = −0.154, t = −7.317, p < 0.01). (2) Physical exercise positively predicted perceived social support (β = 0.218, t = 8.900, p < 0.01) and meaning in life (β = 0.131, t = 6.456, p < 0.01). In turn, perceived social support positively predicted meaning in life (β = 0.513, t = 15.429, p < 0.01) and negatively predicted suicidal ideation (β = −0.243, t = −6.286, p < 0.01). Furthermore, meaning in life exerted a negative effect on suicidal ideation (β = −0.246, t = −5.885, p < 0.01). (3) Both perceived social support and meaning in life significantly mediated the association between physical exercise and suicidal ideation via three pathways: physical exercise → perceived social support → suicidal ideation (mediating effect = −0.053); physical exercise → meaning in life → suicidal ideation (mediating effect = −0.032); and physical exercise → perceived social support → meaning in life → suicidal ideation (mediating effect = −0.028). (4) Gender moderated the effects of physical exercise on meaning in life (β = −0.136, p < 0.01) and on suicidal ideation (β = 0.142, p < 0.01).ConclusionPhysical exercise directly reduces suicidal ideation among college students and indirectly influences it through perceived social support and meaning in life, both as individual mediators and in a sequential pathway. Gender moderates both the initial segment of the physical exercise → meaning in life → suicidal ideation pathway and the direct effect on suicidal ideation.